Toxicant Exposure and Bioaccumulation: A Common and Potentially Reversible Cause of Cognitive Dysfunction and Dementia - Stephen J. Genuis; Kasie L. Kelln (Behavioural Neurology)
Juxtaposed alongside the ongoing rise in the incidence and prevalence of dementia, is the surge of recent research confirming widespread exposure and bioaccumulation of chemical toxicants. Evidence from sources such as the Centers for Disease Control reveals that most people have accrued varying degrees of assorted toxic pollutants including heavy metals, flame retardants, and pesticide residues within their bodies. It has been well established that many of these toxicants have neurodegenerative as well as neurodevelopmental impact as a result of various pathophysiologic mechanisms including neuronal mitochondrial toxicity and disruption of neurotransmitter regulation. Elimination of stockpiled toxicants from the body may diminish adverse toxicant impact on human biology and allow restoration of normal physiological function. Incorporating a review of medical literature on toxicant exposure and dementia with a case history of a lead-exposed individual diagnosed with dementia, this paper will discuss a much overlooked and potentially widespread cause of declining brain function and dementia.